The Impact of Symptoms of Depression, Anxiety, and Low Stress-Coping Capacity on the Effects of Telephone Follow-Up on Recovery Measures After Hysterectomy - Gulnara Kassymova; Gunilla Sydsj?; Ninnie Borendal Wodlin; Lena Nilsson; Preben Kj?lhede (Women's Health Reports, 2024)
Background: To investigate if symptoms of depression, anxiety, and stress-coping capacity have an impact on the effect of telephone follow-up (TFU) on trajectories of six recovery measures after hysterectomy and influence the occurrence of unplanned telephone contacts (uTCs) and unplanned visits (uVs) to health care providers. Material and Methods: A post hoc nonrandomized analysis of participants enrolled in a randomized, four-armed, single-blinded, controlled multicenter intervention study comprising 487 women where the women were allocated 1:1:1:1 to one of four TFU models. The Swedish Postoperative Symptom Questionnaire (SPSQ) and two health-related quality of life questionnaires, the EuroQoL-5 dimension with three levels (EQ-5 D-3?L) and the Short-Form-Health Survey (SF-36) assessed the recovery measures. The six recovery measures consisted of the EQ-5D-3L health index, the SF-36 physical component summary (PCS) and mental component summary (MCS), and the maximum and average pain intensity, and symptom sum score obtained from the SPSQ. Psychological distress was evaluated by the psychometric forms, the Hospital Anxiety and Depression Scale and the Stress Coping Inventory. The occurrence of uTC and uV within the 6 weeks of follow-up was registered. Results: Preoperative anxiety, depression, and stress-coping capacity did not modify the effects of the TFU models on the trajectories of the recovery measures, although anxiety and depression were strongly associated with all six recovery measures. uTCs, but not uVs occurred more often in the women with anxiety. Conclusions: Preoperative anxiety, depression, and stress-coping capacity did not appear to influence the effects of TFU contacts on the recovery measures after hysterectomy. Preoperative anxiety seemed to increase the occurrence of uTC. Clinical Trials Registration: ClinicalTrials.gov (NCT01526668).